ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HUBUNGAN MITRA DENGAN UNIT INDUK PEMBANGUNAN JARINGAN JAWA BALI (UIPJJB) UNTUK MENINGKATKAN KINERJA PROYEK PADA PT. PLN (PERSERO) - Rasyid, Achmad (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2013)
The aims of this research are: first, to investigate the influence of flexibility to UIPJJB- partners cooperation. The second is to investigate the influence of long-term continuity orientation to UIPJJB-partners cooperation. The third is to investigate the influence of communication quality to UIPJJB-partners cooperation. The fourth is to investigate the influence UIPJJB-partners cooperation to PLN project performance.Population of this research is partner companies of UIPJJB PLN. Respondents of 160 are taken with census method. Data are collected with questionnaires using 10 scales. Data are analyzed using Structural Equation Modeling under AMOS 5 program.The result of the data shows that research model has good fit and all the hypotheses can be proved. The conclusions are: flexibility has positive influence to UIPJJB-partners cooperation, long-term continuity orientation has positive influence to UIPJJB-partners cooperation, and communication quality has positive influence to UIPJJB-partners cooperation, and UIPJJB-partners cooperation has positive influence to PLN project performance. Based on the results of the research could be taken theoretical implications that this research gives more justifications for antecedents positively influence UIPJJB- partners cooperation, i.e.: flexibility, long-term continuity orientation, and communication quality. Managerial implications of this research are suggestions to UIPJJB to pay more attention to long-term continuity orientation because this factor is the most dominant factor to build UIPJJB-partners cooperation. Limitation of this research is squared multiple correlation show suboptimal of antecedent variables. Further research need to develop the model with add others antecedent variables.